2011
DOI: 10.4102/ajlm.v1i1.18
|View full text |Cite
|
Sign up to set email alerts
|

Experience of quality management system in a clinical laboratory in Nigeria

Abstract: IssuesQuality-management systems (QMS) are uncommon in clinical laboratories in Nigeria, and until recently, none of the nation’s 5 349 clinical laboratories have been able to attain the certifications necessary to begin the process of attaining international accreditation. Nigeria’s Human Virology Laboratory (HVL), however, began implementation of a QMS in 2006, and in 2008 it was determined that the laboratory conformed to the requirements of ISO 9001:2000 (now 2008), making it the first diagnostic laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…; Audu et al . ). These improvements, partially stimulated by the WHO‐AFRO stepwise accreditation preparedness initiative, have been accompanied by an increase in the number of laboratories in the continent that are engaged in the accreditations process (Mothabeng et al .…”
Section: Policy and Advocacy Eventsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Audu et al . ). These improvements, partially stimulated by the WHO‐AFRO stepwise accreditation preparedness initiative, have been accompanied by an increase in the number of laboratories in the continent that are engaged in the accreditations process (Mothabeng et al .…”
Section: Policy and Advocacy Eventsmentioning
confidence: 97%
“…This process has demonstrated that implementation of a stepwise accreditation preparedness approach can be user-friendly, attractive to all laboratory tiers and developmentally focused while providing a useful mechanism for identifying resource, training, system strengthening needs and target areas for specific interventions (Gershy-Damet et al 2010). Many African states are undertaking changes to strengthen their national laboratory systems (Zeh et al 2010;Audu et al 2012). These improvements, partially stimulated by the WHO-AFRO stepwise accreditation preparedness initiative, have been accompanied by an increase in the number of laboratories in the continent that are engaged in the accreditations process (Mothabeng et al 2012;Maruta et al 2012).…”
Section: Policy and Advocacy Eventsmentioning
confidence: 99%
“…Active patient tracking systems that use social workers to track patients have been applied in Kenya to reduce LTFU among HIV, PMTCT and tuberculosis patients from 21% to 15% [43] . In other studies, peer-based strategies that engage expert and or mentor-mothers in educating and motivating HIV positive mothers to access PMTCT services using their own experience, have been instrumental in improving retention of mother-baby pair in care [58,59] . Interventions should therefore seek to educate mothers and guardians on the grave importance of early diagnosis in pediatric HIV.…”
Section: Discussionmentioning
confidence: 99%
“…QMS are still uncommon in clinical laboratories in Nigeria [6] [7]. In January 2010, implementation of QMS toward WHO-AFRO laboratory accreditation [8] [9] commenced in Nigeria involving several laboratories including Infectious Disease Hospital (IDH), Kano [10], which is supported by FHI360.…”
Section: Introductionmentioning
confidence: 99%